Airport terminal choice model (2014)
Most studies about air travel have dealt with individual issues such as fares, delays and other variables inherent in this mode of transportation, as well as why travelers chose the air mode against other modes, but little has been done to model how a traveler chooses an airport between two available options in a big city. Currently a passenger from the city of Medellin - Colombia to some domestic destinations, has the option of traveling by either of the two airports, Jose Maria Cordova (JMC) or Enrique Olaya Herrera (EOH). This research presents the results of a stated preference survey in a discrete choice experiment, and based on this, a model by destination is obtained; for each one of these models multinomial logit and mixed logit were applied, and evaluated, for each model multinomial logit was chosen as the best.